Identidade e imagem: explorando narrativas iconográficas - Bonifácio Júnior, Nelson Fernandes (2023)
Visual images produced from technical, physical and chemical mediators, fixed and/or moving, have been occupying an increasingly important place, both collectively and individually. Often, they gain the status of reality, not of reproduction of the real. In this context, the design of this work sought to answer the following question: do images contribute to the processes of human construction, replacement, or metamorphosis? Answering the formulated question implied the investigation of the interfaces between images – still and/or moving –, identity processes and human metamorphosis, as well as the relation between the recognition of an image chosen by the subject – regarding the different singular meanings attributed – and the identity metamorphosis experienced, besides the verification of the presence, or not, of emancipatory fragments provided by the relation established between the subject and the representation with specified physical support (photography, cinema, audiovisual, etc.). It was assumed that the images contain senses and meanings: a gesture, a look, a way of smiling, of dressing, and of relating. Therefore, it is appropriate to talk about iconographic narratives, which can contribute to a context in which human metamorphoses take place. That said, it is explicit that visual images played a central role in the thesis, insofar as the collection of life history narratives, the methodology used, was based on the relationship between the subjects and the images they selected, which said something about themselves, their identities, metamorphoses, and, sometimes, emancipatory experiences. Finally, as the research was structured so as to promote the progressive approximation to the guiding question, the conclusion was reached that the physical support images are elements that contribute to human metamorphosis, sometimes acting in a regulatory way, and other times, in an emancipatory way